2020
DOI: 10.1007/s11420-020-09800-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction for Telehealth Physical Therapy Services was Comparable to that of In-Person Services during the COVID-19 Pandemic

Abstract: Background The COVID-19 pandemic has transformed the practice of physical therapy (PT), from a model based on in-person delivery to one that includes telehealth. However, research is needed to assess value, patient satisfaction, and clinical outcomes in the delivery of telehealth PT. Purposes We sought to compare patient satisfaction with in-person and telehealth PT and to determine the factors—such as age, gender, or insurance payer—that contributed to patient satisfaction scores. Methods Patients between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…The effectiveness of care should be defined by patient outcomes—not whether the visit was conducted in person [9]. HSS internal data has shown when patients were asked “How would you rate your confidence that your rehab needs are being met through Telehealth?”, they responded with an average of 4.7 out of 5, with 5 indicating high level of satisfaction [6].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…The effectiveness of care should be defined by patient outcomes—not whether the visit was conducted in person [9]. HSS internal data has shown when patients were asked “How would you rate your confidence that your rehab needs are being met through Telehealth?”, they responded with an average of 4.7 out of 5, with 5 indicating high level of satisfaction [6].…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Ratings of participant and/or clinician experience and satisfaction with telehealth physiotherapy assessments during the COVID-19 pandemic were reported in three of the included utility studies in this review [ 49 , 62 , 64 ]. These papers reported overall good levels of satisfaction with telehealth assessments, one reporting no statistically significant difference in satisfaction levels between face-to-face, telehealth or combined types of services and a higher satisfaction level for participants in the telehealth group for appointment scheduling ( P < 0.001) [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…scored on a 0 to 10 scale with 10 being "most likely" and 0 as "not likely at all." Previous analysis by Eannucci et al [7] found the difference between in-person and telemedicine responses to this question to be approximately 0.10 with standard deviation of 1.2. For our study population, we more conservatively estimated a difference of 0.20 with a standard deviation of 1.5.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 87%
“…To calculate sample size, we used patient satisfaction scores as a primary outcome for the study. Patient satisfaction was operationalized with the question, “How likely is it that you would recommend HSS to friends and family?” scored on a 0 to 10 scale with 10 being “most likely” and 0 as “not likely at all.” Previous analysis by Eannucci et al [7] found the difference between in-person and telemedicine responses to this question to be approximately 0.10 with standard deviation of 1.2. For our study population, we more conservatively estimated a difference of 0.20 with a standard deviation of 1.5.…”
Section: Proposed Methodsmentioning
confidence: 92%